PERENCANAAN PENGGANTI DUDUKAN VALVE PADA SEPEDA MOTOR HONDA CB 100 CC - Oktosatrio, Suhendro; Sugihandoko; TjandraKusuma , Taufan (JURNAL MEKANIKASISTA, 2025)
The Military Academy has high vehicle mobility, particularly motorcycles that are intensively used as a means of transportation within the academy environment. High usage leads to wear and tear on engine components, especially the valve seat, which can affect fuel efficiency and engine power. This study aims to analyze the replacement material for the valve seat on a Honda CB 100 CC motorcycle through material composition testing, hardness testing, and microstructure analysis. The research results indicate that the original valve seat is made of an alloy steel containing chromium and a small amount of nickel, with characteristics similar to the XW-5 material produced by Krakatau Steel. The microstructure analysis reveals a dominance of ferrite and pearlite, which can lead to material brittleness at high temperatures. Therefore, selecting a material that is more heat- and wear-resistant is crucial in designing a replacement valve seat. This study is expected to provide a solution for maintaining and improving the efficiency of motorcycles at the Military Academy while addressing the issue of spare part shortages.